New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. Issue 1 (December 2016) - Suárez-Mozo, Nancy; Hendrickx, Michel
Abstract Background Most species of Polyplacophora are found in shallow, coastal water, and their distribution and ecology is generally well known. On the contrary, information related with distribution, biology and ecology of deep-sea chitons is scarce. Methods Specimens of the deep-sea mollusks fauna were obtained during sampling operations of western Mexico (TALUD project) aimed at the study of invertebrate fauna occurring under the Oxygen Minimum Zone (OMZ). The material reported herein is part of the Polyplacophora fauna collected with a benthic sledge off the west coast of the Baja California Peninsula, in the eastern Pacific, Mexico. Results The deep-sea chitonTripoplax cf.balaenophila Schwabe & Sellanes 2004 was collected in 530–625 m depth, in the following environmental conditions: dissolved oxygen, <0.25 ml/l; temperature, 6.44 °C; salinity, 34.47. It represents a range extension of 63° of latitude (ca 8280 km) to the north for this species previously known only from the type locality, off Concepción, Chile. Conclusions Tripoplax cf.balaenophila is associated with the lower boundary of the Minimum Oxygen Zone occurring off western Mexico, an habitat characterized by severe hypoxic conditions and colonized by well-adapted species that are generally abundant. Assignment of species toTripoplax orLepidozona is still a conflictive issue. The existing discrepancy in slit number and the assignment of "balaenophila " toTripoplax cannot be solved without a more thorough review of both genera. The disjunct distribution of the generaTripoplax in the eastern Pacific is also an interesting biogeographical issue.